ADAPTIVE ALGORITHM FOR RESTORATION OF LOSSY COMPRESSED IMAGES - TOUMI, ABIDA; TERKI, NADJIBA; TALEB AHMED, ABDELMALIK (Courrier du Savoir, 2016)
This work deals with the restoration of lossy compressed image by the use of a metaheuristic which is the Particle Swarm Optimization Algorithm. This algorithm was designed and adopted by the introduction of the Search Efficiency Function for the blind restoration of blurred images and has given excellent results. So, in the present paper we try to apply it in the enhancement of lossy decompressed images, and this application constitutes the contribution of this work. Images used have been compressed by two different compression methods, fractal and JPEG, and with different compression rates. The experimental results obtained were excellent.